Lymphangioma of the Lower Lip—A Diagnostic Dilemma: Report of a Rare Case with a Brief Literature Review - Shamimul Hasan; Syed Ansar Ahmad; Mandeep Kaur; Rajat Panigrahi; Swagatika Panda (Case Reports in Dentistry)
Hamartomas are tumor-like deformities typified by cellular propagation indigenous to the original site, although they display growth arrest without the possibility for further growth. Various hamartomatous oral lesions include hemangiomas, lymphangiomas, nevi, odontomas, Cherubism, etc. Lymphangiomas are benign, developmental hamartomatous entities typified by abnormal proliferation of lymphatic vessels. They are usually congenital, and more than 90% of cases occur by 2 years of age, with a rare occurrence in adults. They have a site affinity for the head and neck, and oral lesions are relatively uncommon. The dorsum of the tongue is the commonest oral site of predilection; however, the lip is a rare site of involvement. Hereby, we present an uncommon case of lymphangioma of the lower lip in a 45-year-old male patient, who reported to our hospital with an asymptomatic lower lip submucosal mass present for the last 3 years. Our case is unique as it occurred on the lower lip of a 45-year-old male. A detailed history and clinical evaluation, ultrasonography, and histopathology confirmed the diagnosis of lymphangioma.